Otimização da transesterificação enzimática do óleo de macaúba assistida por ultrassom - Gonçalves, Diogo Palermo (Universidade Estadual Paulista (Unesp), 2022)
Given the current scenario, one of the fundamental pillars for environmental degradation is the excessive use of fossil fuels. Besides the high dependency and the possible future unavailability, the use from this generates impacts to nature, such as the discharge of harmful gases into the atmosphere, the greenhouse gases. Therefore, the availability of new technologies as energy alternatives, especially biofuels, is necessary. The present work aims at the production of biodiesel from the oil of the macaúba palm (Acrocomia aculeata). This oleaginous plant presents excellent characteristics for biodiesel production, such as high availability, high oil content, scalability and resistance. The conversion process used in this work was the transesterification reaction by enzymatic catalysis using the biocatalyst Lipozyme RM IM and having methanol as the transesterifying agent. The reaction also investigated the use of ultrasonic waves as a process enhancer. To determine the best reaction conditions a 2³ experimental design was used, being the independent variables time (t), temperature (T) and catalyst concentration (C) and the dependent variable the yield in esters. The concentrations of methanol and almond oil remained constant (molar ratio oil:methanol 1:6), as well as the wave frequency of the ultrasonic bath (40kHz). The quantification of the obtained esters was performed by gas chromatography. The study range that obtained the best efficiency had as levels used time of 6 hours, temperature of 45ºC and concentration of biocatalyst close to 10% (m/m) in which a yield of 85.4% was obtained. Based on the results obtained as acidity index, composition and reaction conditions it is possible to conclude that biodiesel derived from oil of the macaúba palm presents itself as a viable alternative as a renewable fuel, scalable and when compared to fossil fuels, present less environmental impact.

Diante do atual cenário, um dos pilares fundamentais para degradação ambiental é a utilização excessiva dos combustíveis de origem fóssil. Além da alta dependência e a possível indisponibilidade futura, o uso a partir dessa gera impactos à natureza, tais como a descarga de gases nocivos à atmosfera, os gases de efeito estufa. Sendo assim, é necessária a disponibilização de novas tecnologias como alternativas energéticas, em especial os biocombustíveis. O presente trabalho tem como objetivo a produção de biodiesel a partir do óleo da amêndoa da macaúba (Acrocomia aculeata). Tal oleaginosa apresenta características excelentes para produção de biodiesel, como alta disponibilidade, alto índice de óleo, escalabilidade e resistência. O processo de conversão utilizado neste trabalho foi a reação de transesterificação por meio da catálise enzimática com uso do biocatalisador Lipozyme RM IM e tendo como agente transesterificante o metanol. A reação também investigou a utilização das ondas ultrassônicas como potencializador do processo. Para a determinação das melhores condições reacionais foi utilizado um planejamento experimental 2³, sendo as variáveis independentes o tempo (t), a temperatura (T) e a concentração de catalisador (C) e a variável dependente, o rendimento em ésteres. As concentrações de metanol e óleo da amêndoa permaneceram constantes (razão molar óleo:metanol de 1:6), assim como a frequência de onda do banho ultrassônico (40kHz). A quantificação dos ésteres obtidos foi realizada por cromatografia gasosa. A faixa de estudo que obteve a melhor eficiência teve como níveis utilizado tempo de 6 horas, a temperatura de 45ºC e a concentração de biocatalisador próximo a 10% (m/m) em que se obteve um rendimento de 85,4%. Com base nos resultados obtidos como índice de acidez, composição e condições reacionais é possível concluir que o biodiesel derivado do óleo da amêndoa da macaúba se apresenta como uma alternativa viável como combustível renovável, escalável e quando comparado aos fósseis, apresentar menor impacto ambiental.
Optimization of ultrasound-assisted enzymatic transesterification of macauba oil
Keywords: Biodiesel; Biocombustíveis; Óleos vegetais; Macaúba; Biocatálise